2013
DOI: 10.1088/0741-3335/55/3/035003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of compact torus injection on toroidal flow in the STOR-M tokamak

Abstract: In compact torus injection (CTI) experiments on the STOR-M tokamak, an ion Doppler spectrometer is installed to observe the effects of CTI on toroidal plasma flows. The intrinsic toroidal flow in ohmic discharges without CTI is sheared with counter plasma current flow in the core region and co-current direction at the periphery. With tangential CTI along the co-current direction, the flow velocity in the core region decreases by more than 5 km s −1 , while in the periphery the flow velocity increases by 3-4 km… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Suppression of the m = 2 MHD mode and transition to improved plasma confinement (H-mode) after tangential CTI have been observed [7]. It has also been recently found that the toroidal flow velocity can be modified by tangential CTI [5] and RMP fields [11] along with suppression of MHD fluctuations. In both RMP and tangential CTI cases, the change of the toroidal flow velocity was in the counter-clockwise (CCW, top view) direction, coincide with both CT injection direction and the plasma current direction.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Suppression of the m = 2 MHD mode and transition to improved plasma confinement (H-mode) after tangential CTI have been observed [7]. It has also been recently found that the toroidal flow velocity can be modified by tangential CTI [5] and RMP fields [11] along with suppression of MHD fluctuations. In both RMP and tangential CTI cases, the change of the toroidal flow velocity was in the counter-clockwise (CCW, top view) direction, coincide with both CT injection direction and the plasma current direction.…”
Section: Introductionmentioning
confidence: 89%
“…The most probable location for the O V emission is around r = 3 cm. The IDS system for the STOR-M tokamak has a velocity resolution of ≈ v 1-2 km s −1 [5], determined by the range of the fluctuating spectral peak locations when the line of sight of the IDS system is in the minor radial direction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among various tools of magnetic confinement, tokamak containing hot plasma is one of the best and developed devices [1]. Tokamaks are divided into two groups: first, the large tokamaks for studying large plasmas such as DIII-D [2] and Tore-Supra [3] with high-cost testing conditions and second, small tokamaks such as STOR-M [4] and ISTTOK [5] which have close relationship with the first group so that most of the experiments are initially carried out by them. One of the applications of tokamaks is in the field of nanoscience.…”
Section: Introductionmentioning
confidence: 99%
“…In tokamaks, intrinsic countercurrent rotation is frequently observed in ohmic discharges. However, in some machines [9][10][11][12], co-current rotation is also observed at the plasma edge. In addition to the models that assume that momentum might be generated by the turbulence, during gas injection the radial friction force between neutral particles and ions/electrons, taking into account the poloidal magnetic field, may also drive toroidal rotation.…”
Section: Introductionmentioning
confidence: 99%